Distribution of time to buffer overflow in a finite-buffer manufacturing model with unreliable machine - Kempa, Wojciech M.; Paprocka, Iwona; Grabowik, Cezary; Kalinowski, Krzysztof; Krenczyk, Damian (MATEC web of conferences, 2017)
One of the most important characteristic of each queueing model is time to buffer overflow. In the paper the distribution of that time in a single-channel manufacturing system, modelled by a Markovian finite-buffer queue with machine breakdowns, is studied. By using the analytical approach based on the idea of embedded Markov chain, total probability law and linear algebra, the formula for Laplace transform of the time to buffer overflow conditional distribution is found. Numerical illustration is presented.